Analisis Pengaruh Harga Dan Promosi Terhadap Keputusan Konsumen Dalam Pembelian Produk Online Di Bukalapak - roswaty, roswaty (Jurnal Keuangan dan Bisnis, 2022)
The objective of this research was to determine the influence of prices and promotions on online goods purchasingdecisions at Bukalapak with purchases concentration on fashion products. The tests were administered to 60 peopletaken by using non probability sampling techniques, while the determination of respondents was taken through asaturated sampling method. The technical analysis calculation was done by using the t test method, correlation test,determination test and multiple linear regression test. The results of the t test showed that t count of X1 (price) was2.498 at the level of sig 0.015 and t count of X2 (promotion) was 2.043 at the level of sig 0.048. The results of thecorrelation test indicated that Y and X1 were 0.386, Y and X2 were 0.318. The result of the determination test was0.682. The results of the multiple linear regression tests were Y = 2.264 + 0.263 + 0.218. The results of this researchrevealed that prices and promotions had a positive influence on goods purchasing decisions. The most influential factorin purchasing decisions online at Bukalapak was Promotion. Price factor remains a significant contributor for thepresentation of purchasing decision, because in Bukalapak can be made of bargaining system. Assessment ofsatisfaction in the Bukalapak application on 19 March 2020 at 11am on Playstore show a rating 4,5 of 5,0 with a totalrating of 922.968 people. Bukalapak must maintain the price level by working with MSMEs and making several newpromotions.Key word : Price, Promotion, Consumer Decision